TRANSFORMATION OF DAKWAH COMMUNICATION IN FORMING MODERATE ATTITUDES, AN ANALYSIS STUDY OF AL URWATUL WUTSQO 2 ISLAMIC BOARDING SCHOOL - Moh Zahiq (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The study aims to analyze the transformation of da'wah communication in forming moderate attitudes at the Al Urwatul Wutsqo 2 Islamic Boarding School, Wlingi, Blitar. With a qualitative approach, this study examines how da'wah messages are delivered and their influence on the moderation of santri's attitudes. Data were obtained through interviews, observations, and documentation. The results show that the use of digital media and a dialogical approach in da'wah has been effective in forming moderate, tolerant, and inclusive attitudes among santri. This transformation shows the importance of adapting da'wah communication methods in responding to the challenges of the times.